Here's the question you clicked on:
thihaaung
The vertex form of the equation of a parabola is y = 5(x - 3)2 - 6. What is the standard form of the equation? pic - http://i.imgur.com/ekbjOQH.png
Okay so here;s the steps! \[5(x-3)^{^{2}} -6\] the you get 5(x-3)(x-3)-6 then you get \[5(x ^{2} -3x-3x+9)\] then multiply 5 \[(5x ^{2} -30x +45) -6\] the last step is 45-6 is 39 so your answer will be... \[5x ^{^{2}} -30x +39\]
@linda3 thank you! ;)
your most very welcome!
another approach vertex (h, k) h = -b/2 a and k =- a(-b/2 a)^2 + c a = 5 3 = -b/2*5 so b =-30 (-b/2a)^2 =(-30/10)^2 = 9 -6 = -5(9)+ c so c = 45 - 6 = 39 5 x^2 -30 x + 39
@triciaal thank you!! ;)